Pengaruh Modal, Jenis Usaha, Pelatihan, dan Tata Kelola Terhadap Produktivitas dan Pendapatan BUMDes di Kabupaten Tabanan - Miamithadewi, Ni Putu Anggun; Purwanti, Putu Ayu Pramitha (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze: 1) the influence of capital, type of business, training and governance on BUMDes productivity in Tabanan Regency 2) the influence of capital, type of business, training, governance and productivity on BUMDes income in Tabanan Regency 3) the influence of no direct capital, type of business, training, and governance on income through BUMDes productivity in Tabanan Regency. This research uses an associative quantitative approach. This research was conducted in Tabanan Regency, the number of samples used was 31 respondents using a saturated sampling method (census method). The data collection methods used in this research are: observation, interviews and in-depth interviews. Hypothesis testing uses path analysis with factor scores and Sobel test. The results of this research show that capital and governance directly have a positive and significant effect on productivity, while type of business and training do not directly have a significant effect on BUMDes productivity in Tabanan Regency. Training and productivity directly have a positive and significant effect on income, while capital, type of business and governance do not directly have a significant effect on BUMDes income in Tabanan Regency. Capital and governance have an indirect influence on income through productivity in Tabanan Regency, while type of business and training have no effect on income through productivity.